Augmented-reality swim goggles accurately and reliably measure swim performance metrics in recreational swimmers - Eisenhardt, D.; Kits, A.; Madeleine, P.; Samani, A.; Clarke, D. C.; Kristiansen, M. (Frontiers in Sports and Active Living, 2023)
Background: Swimmers commonly access performance metrics such as lap splits, distance, and pacing information between work bouts while they rest. Recently, a new category of tracking devices for swimming was introduced with the FORM Smart Swim Goggles (FORM Goggles). The goggles have a built-in see-through display and are capable of tracking and displaying distance, time splits, stroke, and pace metrics in real time using machine learning and augmented reality through a heads-up display. The purpose of this study was to assess the validity and reliability of the FORM Goggles compared with video analysis for stroke type, pool length count, pool length time, stroke rate, and stroke count in recreational swimmers and triathletes.